DNA methylation, histone acetylation and methylation of epigenetic modifications as a therapeutic approach for cancers. Issue 2 (10th April 2016) - Yen, Ching-Yu; Huang, Hurng-Wern; Shu, Chih-Wen; Hou, Ming-Feng; Yuan, Shyng-Shiou F.; Wang, Hui-Ru; Chang, Yung-Ting; Farooqi, Ammad Ahmad; Tang, Jen-Yang; Chang, Hsueh-Wei
Highlights: This review summarizes the roles of epigenetic modification. Epigenetic modification connects gene regulation, cancer, sugar metabolism, ROS, carcinogenesis, and therapeutic targets. We discuss the combined treatment of epigenetic regulator and cancer therapy. We highlight ongoing efforts in the epigenetic modification field into cancer therapy. Abstract: Epigenetic modifications play important roles in regulating carcinogenesis, and specific epigenetic modifications have emerged as potential tumor markers. Herein, we summarize several types of epigenetic modifications, explore the role played by epigenetic modifications in gene regulation, and describe the patterns of epigenetic modifications in cancers. Since epigenetic modifications have been reported to regulate the Warburg effect in cancers, the roles of epigenetic modifications in sugar metabolism are discussed. In addition, oxidative stress may play an important role in carcinogenesis, and the role of oxidative stress and epigenetic modification in carcinogenesis is addressed. We also discuss the role of epigenetic modifications as therapeutic targets. Finally, the synergistic effects of the combined treatment of epigenetic regulator and anticancer drugs for cancer therapy are described.